Operating system use Pattern in Accessing a Digital Marketing Content Posted in LinkedIn - Kuberappa, Yamuna V; HS Kumar, Arun (Biology, Engineering, Medicine and Science Reports)
Digital marketing has gained increasing momentum with the collateral surge in popularity of online media. In this context, knowledge about the operating systems used to access such digital content is vital, as this will help optimally formulate the digital content to ensure its compatibility with the operating systems used. Hence we analysed the pattern of operating systems used to access digital marketing content posted in one of our platforms in LinkedIn. We provide here a relative frequency of different operating systems used, which we believe will be useful for all those involved in designing digital marketing content.
Keywords: Operating system; Digital marketing; Analysis; Microsoft; Apple OS; Linux; Consumer dynamics